2020
DOI: 10.1038/s41598-020-73187-w
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ gaze exhibits a fractal structure that varies by age and stimulus salience

Abstract: The development of selective visual attention is critical for effectively engaging with an ever-changing world. Its optimal deployment depends upon interactions between neural, motor, and sensory systems across multiple timescales and neurocognitive loci. Previous work illustrates the spatio-temporal dynamics of these processes in adults, but less is known about this emergent phenomenon early in life. Using data (n = 190; 421 visits) collected between 3 and 35 months of age, we examined the spatio-temporal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
(90 reference statements)
1
9
0
Order By: Relevance
“…On the other hand, the current results revealed no impact of perceptual salience on STM performance at earlier and later childhood (6 and 10 years, respectively). This latter finding appears to be consistent with those studies supporting an increased influence of perceptual salience to predict eye movements and overt exploration as a function of age 29 , 31 35 . However, it might be also possible that—as an alternative account—performance differences between children and adults arose not at the encoding, but at the following stages, namely, at maintenance, e.g.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the current results revealed no impact of perceptual salience on STM performance at earlier and later childhood (6 and 10 years, respectively). This latter finding appears to be consistent with those studies supporting an increased influence of perceptual salience to predict eye movements and overt exploration as a function of age 29 , 31 35 . However, it might be also possible that—as an alternative account—performance differences between children and adults arose not at the encoding, but at the following stages, namely, at maintenance, e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Some of these studies reported that salience is a better predictor for adults’ than for infants’ eye movements 29 , showing that, in general, the predictive value of perceptual salience increases as a function of age (e.g. 30 35 ). However, other studies reported the opposite pattern of results.…”
Section: Introductionmentioning
confidence: 99%
“…The first is an oscillatory 'foraging' component which triggers reorientations at regular time intervals. Evidence for such a component has been shown using modelling work looking at saccade generation timing with adults 176,177 and infants 178 as well as at a larger temporal scale, between attention episodes on a time-scale of seconds 58,59,179,180 . These periodic attention shifts, which are often associated with oscillatory fluctuations in perceptual sensitivity 86,88 , are comparable to animals' rhythmic sampling of the environment through whisking (Kleinfeld, Deschênes, & Ulanovsky, 2016), sniffing (Ahrens & Kleinfeld, 2004) and licking (Amarante, Caetano, & Laubach, 2017).…”
Section: Figure 5: Schematic Illustrating Negative and Positive Feedback Loops As Commonly Used In Electronics Which Can Be Used As A Metmentioning
confidence: 99%
“…Other recent findings using a reinforcement learning paradigm have found that 9‐month‐old infants are biased to use social information (female faces), over non‐social information (colorful shapes), to organize hierarchical rule representations that support behavioral flexibility, presumably due to the intrinsic reward value of social stimuli (Werchan & Amso, 2021). Similarly, infants ages 3–35 months show greater self‐organized, hierarchical patterns of visual attention when viewing salient social information, relative to degraded social information (Stallworthy et al., 2020), likely due to the value of this information for learning and survival. Over time, repeated activation of reward systems to parental‐related cues may scaffold children's trait‐level reward responsivity.…”
Section: Sensitive Caregiving and Reward Processingmentioning
confidence: 99%